Why We Should Strive For A Toxin-Free Mouth - Doepp, Manfred (British Journal of Healthcare and Medical Research, 2024)
In addition to other factors, intoxication from foreign substances that the body does not need, but which burden it, are harmful to the organism. They lead to organ weaknesses and reduce life expectancy. Nowadays, the oral cavity has become an important source of toxins. This concerns light and heavy metals on the one hand and cadaveric toxins from dead tissue on the other. In addition, foci in the mouth have the ability to disrupt and block the regulation of organ functions. Tooth roots and the adjacent jawbones are more important than the teeth themselves. Non-infectious chronic jawbone osteitis, for example, can be a risk factor for cancer. These facts should prompt us all to strive for a toxin-free mouth.